Solid state fermentation of soybean hulls for cellulolytic enzymes production: physicochemical characteristics, and bioreactor design and modeling - Brijwani, Khushal (Kansas State University, 2011)
The purpose of this study was to investigate micro- and macro-scale aspects of solid state fermentation (SSF) for production of cellulolytic enzymes using fungal cultures. Included in the objectives were investigation of effect of physicochemical characteristics of substrate on enzymes production at micro-scale, and design, fabrication and analysis of solid-state bioreactor at macro-scale. In the initial studies response surface optimization of SSF of soybeans hulls using mixed culture of Trichoderma reesei and Aspergillus oryzae was carried out to standardize the process. Optimum temperature, moisture and pH of 30ºC, 70% and 5 were determined following optimization. Using optimized parameters laboratory scale-up in static tray fermenter was performed that resulted in production of complete and balanced cellulolytic enzyme system. The balanced enzyme system had required 1:1 ratio of filter paper and beta-glucosidase units. This complete and balanced enzyme system was shown to be effective in the hydrolysis of wheat straw to sugars. Mild pretreatments– steam, acid and alkali were performed to vary physicochemical characteristics of soybean hulls – bed porosity, crystallinity and volumetric specific surface. Mild nature of pretreatments minimized the compositional changes of substrate. It was explicitly shown that more porous and crystalline steam pretreated soybean hulls significantly improved cellulolytic enzymes production in T. reesei culture, with no effect on xylanase. In A. oryzae and mixed culture this improvement, though, was not seen. Further studies using standard crystalline substrates and substrates with varying bed porosity confirmed that effect of physicochemical characteristics was selective with respect to fungal species and cellulolytic activity. A novel deep bed bioreactor was designed and fabricated to address scale-up issues. Bioreactor’s unique design of outer wire mesh frame with internal air distribution and a near saturation environment within cabinet resulted in enhanced heat transfer with minimum moisture loss. Enzyme production was faster and leveled within 48 h of operation compared to 96 h required in static tray. A two phase heat and mass transfer model was written that accurately predicted the experimental temperature profile. Simulations also showed that bioreactor operation was more sensitive to changes in cabinet temperature and mass flow rate of distributor air than air temperature.
Keywords: Trichoderma reesei; Aspergillus oryzae; Crystallinity; bed porosity; Solid-state bioreactor; N-tank in series model; Food Science (0359)